Risk and protective factors for physical and emotional abuse victimisation amongst vulnerable children in South Africa - Meinck, F; Cluver, L; Boyes, M; Ndhlovu, L (John Wiley and Sons, Ltd, 2015)
Little is known about risk and protective factors for emotional and physical child abuse in South Africa. Existing research has focused largely on sexual abuse and relied on recollections of childhood abuse from university and high-school students or data from criminal reports. The objective of this study was to establish risk and protective factors for severe physical and emotional abuse amongst a large cross-sectional community sample of South African youth. Confidential self-report questionnaires were completed by children aged 13-19 (n=603, 47.9% female) with local interviewers in deprived areas of South Africa. Standardised measures of abuse, hypothesised risk factors and socio-demographic variables were used. Factors associated with severe physical and emotional child abuse were experience of family conflict (p=0.003), unequal food distribution (p<0.014), inconsistent discipline (p=0.012), number of caregiver changes (p=0.022), living with a step-parent (p=0.034), caregiver disability (p=0.004), food insecurity (p=0.006), bullying (p<0.001), acquired immunodeficiency syndrome (AIDS)-related stigma (p<0.001), sexual abuse (p=0.003), school non-attendance (p=0.006) and non-achievement (p=0.015). These identified risk and protective factors at community, school, caregiver and household levels have the potential to affect the risk of abuse for children in South Africa, and may be valuable fields for future intervention efforts.